Recent Trends in Graphene-Based Sorbents for LC Analysis of Food and Environmental Water Samples - João V. B. Borsatto; Fernando M. Lanças (Molecules, 2023)
This review provides an overview of recent advancements in applying graphene-based materials as sorbents for liquid chromatography (LC) analysis. Graphene-based materials are promising for analytical chemistry, including applications as sorbents in liquid chromatography. These sorbents can be functionalized to produce unique extraction or stationary phases. Additionally, graphene-based sorbents can be supported in various materials and have consequently been applied to produce various devices for sample preparation. Graphene-based sorbents are employed in diverse applications, including food and environmental LC analysis. This review summarizes the application of graphene-based materials in food and environmental water analysis in the last five years (2019 to 2023). Offline and online sample preparation methods, such as dispersive solid phase microextraction, stir bar sorptive extraction, pipette tip solid phase extraction, in-tube solid-phase microextraction, and others, are reviewed. The review also summarizes the application of the columns produced with graphene-based materials in separating food and water components and contaminants. Graphene-based materials have been reported as stationary phases for LC columns. Graphene-based stationary phases have been reported in packed, monolithic, and open tubular columns and have been used in LC and capillary electrochromatography modes.